2021
DOI: 10.1177/09596801211052531
|View full text |Cite
|
Sign up to set email alerts
|

With or without U(nions)? Understanding the diversity of gig workers’ organizing practices in Italy and the UK

Abstract: Since 2016, mobilizations of gig workers across European countries have become increasingly common within location-based services, such as food delivery. Despite remarkable similarities in workers’ mobilization dynamics, their organizational forms have varied considerably, ranging from self-organization, to work councils, to unionization through rank-and-file or longstanding unions. To start making sense of this diversity in organizing practices, we compare two cases of mobilization in the food delivery sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…In a similar way, Saundry et al (2007) found that the creative workers they studied used the information on forum members’ shared experiences of specific employers to bargain more effectively. Banding together to create resource repositories may also unite workers in ways that help them feel as though they are gaining power and security which can often be depleted through algorithmic management (Wood et al, 2018), and may even help with union organizing (Blagoev et al, 2019; Cini et al, in press; Maffie, 2020).…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
“…In a similar way, Saundry et al (2007) found that the creative workers they studied used the information on forum members’ shared experiences of specific employers to bargain more effectively. Banding together to create resource repositories may also unite workers in ways that help them feel as though they are gaining power and security which can often be depleted through algorithmic management (Wood et al, 2018), and may even help with union organizing (Blagoev et al, 2019; Cini et al, in press; Maffie, 2020).…”
Section: Adapting To Gig Work: Implications For Organizations and For...mentioning
confidence: 99%
“…Meanwhile, comparative research findings show the importance of a combination of grassroots organizing (Joyce and Stuart, 2021) and new approaches to building solidarity – not only among gig workers themselves (Tassinari and Maccarrone, 2020; Cini et al 2021) but also among the organizations representing them. Vandaele (2021: 206) argues that the platform economy’s ‘distinctively disordered nature’ encourages creativity and experimentation in labour relations; particularly encouraging cooperation between established unions and newer, more informally organized worker representatives.…”
Section: Cer and Digitalizationmentioning
confidence: 99%
“…We find not only that young people engage to a low extent through formal mechanisms of participation (Blais et al 2004;Dalton 2009) but also that party loyalties and attachments are less stable among the younger cohorts. It has been noted that young people were overrepresented among protesters against precarious work and racism (Cini et al 2022;Della Porta 2019). A recent study found that parties with strong ties to civil society organizations have a more stable voter base (Martin et al 2022).…”
Section: Resultsmentioning
confidence: 99%